STRATEGI PENGEMBANGAN DESA PINGE SEBAGAI DESA WISATA DI KECAMATAN MARGA KABUPATEN TABANAN BALI - Agnes Rai Madalena; L.K Herindyah Kartika Yuni; Ni Wayan Mekarini (Universitas Triatma Mulya, 2021)
This research was conducted in Pinge Tourism Village which is one of the Tourism Villages in Tabanan Regency, determined based on the decision of the Tabanan Regent No. 337 of 2004 dated July 18, 2004. This research was done in aim to know the internal and external potential in Pinge Village as a tourism village (2) to find out the development strategy of Pinge Village as a tourism village. The reaserch method used descriptive qualitative methods. that are: (1) determination location of the research; (2) information selection techniques; methods of data collection (observation, interviews, document studies) and SWOT analysis (strengths, weaknesses, opportunities, threats), namely: using the IFAS, EFAS and SWOT matrices. The presentation technique of the results of the analysis is in the form of description by giving in detail. The internal potential contained in the results of this research consisted of: natural potential in the form of a beautiful natural atmosphere after subak irrigation, spatial planning, arts, crafts, cultural activities, religious rituals, and archaeological sites. The external potential of the results of this study consisted of adequate accessibility, support & partnerships, facilities, and the existence of POKDARWIS as a community organization in village development. With the constraints and threats encountered in the form of human resource skills that are less competent and have not participated as a whole, the lack of public facilities and support and promotional activities undertaken. This can provide a formulation of development strategies to optimize the strengths and opportunities available to overcome weaknesses and threats in development.